Co-utilization of reactivated cement pastes with coal gangue. (8th February 2021) - Shi, Xuyang; Cai, Qingxiang; Qi, Chongchong; Zhang, Linglei; Lu, Xiang; Zhou, Wei; Zhao, Binyu
Highlights: A new strategy is proposed for the co–utilization of HCP and CG. The grinding effect and reactivity of HCP is improved by CG. Flowability, mechanical properties, phase composition, and FT-IR are studied. The effect of CG on the water requirement and hydration reaction is discussed. Abstract: The disposal of cement-based construction waste and the reduction in cement consumption are two bottlenecks for the cement and concrete industry. However, these two issues can be tackled simultaneously through reactivating hydrated cement paste (HCP) to be used as new cementitious materials. Moreover, the reactivated HCP can be used together with other solids waste, such as coal gangue (CG), to improve the grinding effect and reactivity. This study aims to investigate the co-utilization of HCP and CG with special focus on its flowability, mechanical properties, phase composition and hydration mechanism. It has been found that the addition of CG could increase the grinding time before agglomeration happened (from 6 min at 0% CG to 15 min at 15% CG and 35 min at 30% CG). Therefore, the final grain size of solid particles was decreased after CG addition. Partial replacement of ordinary Portland cement with HCP and CG could lead to a decrease in the flowability (between 2.3% and 7.1% depending on the HCP to CG proportion). The flowability was further decreased after the calcination. The strength of the mortar was also decreased after HCP + CG replacement (between 21.6% and 36.6%). However, the calcination activation promoted strength development. XRD and FT-IR results indicate the HCP calcination led to the generation of lime and β-C2 S, the content of which had a positive correlation with the calcination temperature. The addition of CG resulted in a decrease of the lime content and the generation of new mineralogical phases, including quartz and mayenite.